Vanadium Oxide Thin Film Temperature Microsensor - Kramar, María Belén (2025)
Vanadium oxides are known for their thermal properties, such as high temperature coefficient of resistance (TCR). This article presents the development of a low-cost and easy-to-fabricate temperature microsensor, specially designed to be integrated into microfluidic channels, although it can be used in multiple applications. It consists of a thin film of vanadium oxide as a resistive sensor on glass substrates. Two meander-shaped geometries with an area less than 1,5 mm2 were designed and microfabricated. A steady-state and dynamic thermal characterization was performed to determine its specifications. The sensors demonstrated linear behaviour and an average TCR of 4055 ppm/°C was obtained for a temperature range of 20 to 75 °C.